Influência da suplementação dietética com luteína sobre a progressão e no tratamento da periodontite experimental induzida em ratos - Vitória, Otávio Augusto Pacheco [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O propósito deste estudo foi de avaliar os efeitos da suplementação dietética com luteína (LT) na progressão no tratamento da periodontite experimental (PE). 120 ratos machos (Wistar) foram divididos em quatro grupos. A indução da PE foi realizada por meio da instalação de uma ligadura de algodão no primeiro molar inferior esquerdo. Grupos: ST-SS (n=30): 0,7 ml/kg de SS via gavagem gástrica (GG) diariamente. ST-LT (n=30): GG com 250mg/kg de LT, por todo período experimental. RAR-SS: 0,7 ml/kg de SS via GG diariamente, após 7 dias a RAR é realizada. RAR-LT: LT via GG diariamente, após 7 dias a RAR foi realizada. A eutanásia foi realizada aos 7, 15 e 30 dias após a indução de PE (ST-SS e ST-LT) ou RAR (RAR-SS e RAR-LT). As hemimandíbulas foram removidas e submetidas ao processamento por desmineralização para análise histométrica para porcentagem de osso na furca (POF), análise histopatológica da região de furca, análise imunohistoquímica para detecção da IL-1β, TNFα, IL-10, TRAP e OCN. Os dados foram submetidos ao teste de Shapiro-Wilk, análise de variância (ANOVA) e pós-teste de Tukey (p≤0,05). Menor POF foi observado no grupo RAR/SS 7, 15 e 30 dias em relação ao grupo RAR/LT em todos os períodos (p<0,05). Não foram observadas diferenças da POF no grupo ST/LT 7, 15 e 30 dias quando comparado ao grupo RAR/SS nos mesmos períodos. Na análise histopatológica, menor intensidade e extensão do processo inflamatório assim como maior estruturação do tecido conjuntivo e ósseo na região de furca foi observado no grupo RAR/LT e ST/LT aos 7, 15 e 30 dias quando comparado com o grupo RAR/SS e ST/SS nos mesmos períodos. Na análise imunoistoquímica, o grupo ST/LT 30 dias apresentou menor número de células TRAP-positivas quando comparadas ao grupo RAR/SS e RAR/LT no mesmo período (p<0,05). O grupo RAR/SS 7 dias apresenta maior número de células TRAP-positivas em relação ao grupo RAR/LT no mesmo período (p<0,05). O grupo ST/LT 30 dias apresentou maior densidade de imunomarcação para OCN quando comparado com o grupo RAR/LT no mesmo período (p<0,05). O grupo ST/LT 15 e 30 dias apresenta maior densidade de imunomarcação para OCN quando comparado com o grupo RAR/SS nos mesmos períodos (p<0,05). O grupo RAR/SS 15 e 30 dias apresentaram maior densidade de imunomarcação para IL-1β em relação ao grupo RAR/LT nos mesmos períodos (p<0,05). O grupo ST/LT 7, 15 e 30 dias apresentou menor densidade de imunomarcação para IL-1β em relação ao RAR/SS nos mesmos períodos (p<0,05). O grupo RAR/SS 15 e 30 dias apresentou menor densidade de imunomarcação para IL-10 quando comparado com o grupo RAR/LT nos mesmos períodos (p<0,05). O grupo ST/LT 30 dias apresentou maior densidade de imunomarcação para IL-10 em relação ao grupo RAR/SS 30 dias (p<0,05). O grupo ST/LT 7 dias apresentou menor densidade de imunomarcação para TNFα em comparação ao grupo RAR/SS 7 dias e RAR/LT 7 dias. Conclui-se que a LT se mostrou efetiva no controle da progressão da PE e quando associada a RAR, apresentou melhores resultado em comparação a SS adjuvante a RAR.

The purpose of this study was to evaluate the effects of dietary lutein (LT) supplementation on progression in the treatment of experimental periodontitis (EP). 120 male rats (Wistar) were divided into four groups. PE induction was performed by installing a cotton ligature on the lower left first molar. Groups: ST SS (n=30): 0.7 ml/kg of SS via gastric gavage (GG) daily. ST LT (n=30): GG with 250mg/kg of LT, for the entire experimental period. RAR SS: 0.7 ml/kg of SS via GG daily, after 7 days RAR is performed. RAR LT: LT via GG daily, after 7 days RAR was performed. Euthanasia was performed at 7, 15 and 30 days after PE (ST SS and ST LT) or RAR (RAR SS and RAR LT) induction. The hemimandibles were removed and submitted to demineralization processing for histometric analysis for percenta ge of bone in the furcation (POF), histopathological analysis of the furcation region, immunohistochemical analysis for detection of IL 11β, TNF TNFα, IL 10, TRAP and OCN. Data were submitted to test Shapiro wilk, analysis of variance (ANOVA) and Tukey's post t est (p≤0.05). Lower POF was observed in the RAR/SS group 7, 15 and 30 days compared to the RAR/LT group in all periods (p<0.05). No POF differences were observed in the ST/LT 7, 15 and 30days group when compared to the RAR/SS group in the same periods. In the histopathological analysis, lower intensity and extension of the inflammatory process, as well as greater structuring of connective and bone tissue in the furcation region, was observed in the RAR/LT and ST/LT group at 7, 15 and 30 days when compared t o the RAR/SS group and ST/SS in the same periods. In the immunohistochemical analysis, the ST/LT 30 days group had a lower number of TRAP positive cells when compared to the RAR/SS and RAR/LT groups in the same period (p<0.05). The 7 day RAR/SS group has a higher number of TRAP positive cells than the 7 day RAR/LT group (p<0.05). The ST/LT 30 days group showed a higher density of immunostaining for OCN when (p<0.05). The ST/LT 30 days group showed a higher density of immunostaining for OCN when compared to the RAR/LT group in the same period (p<0.05). The ST/LT 15 and 30 days group compared to the RAR/LT group in the same period (p<0.05). The ST/LT 15 and 30 days group showed a higher density of immunostaining for OCN when compared to the RAR/SS showed a higher density of immunostaining for OCN when compared to the RAR/SS group in group in the same periods (p<0.05). The RAR/SS 15 and 30 days group showed higher immunostaining the same periods (p<0.05). The RAR/SS 15 and 30 days group showed higher immunostaining density for ILdensity for IL--11β compared to the RAR/LT group in the same periods (p<0.05). The ST/LT 7, compared to the RAR/LT group in the same periods (p<0.05). The ST/LT 7, 15 and 30 days group showed lower immunostaining density for IL15 and 30 days group showed lower immunostaining density for IL--11β cocompared to RAR/SS mpared to RAR/SS in the same periods (p<0.05). The 15 and 30 days RAR/SS group showed a lower in the same periods (p<0.05). The 15 and 30 days RAR/SS group showed a lower immunostaining density for ILimmunostaining density for IL--10 when compared to the RAR/LT group in the same periods 10 when compared to the RAR/LT group in the same periods (p<0.05). The ST/LT 30 days group showed a higher immunostaining density fo(p<0.05). The ST/LT 30 days group showed a higher immunostaining density for ILr IL--10 10 compared to the RAR/SS 30 days group (p<0.05). The 7compared to the RAR/SS 30 days group (p<0.05). The 7 day ST/LT group had a lower day ST/LT group had a lower immunostaining density for TNFimmunostaining density for TNFα compared to the 7compared to the 7--day RAR/SS and 7day RAR/SS and 7 day RAR/LT group. day RAR/LT group. It is concluded that LT proved to be effective in controlling the progression of PIt is concluded that LT proved to be effective in controlling the progression of PE and when E and when associated with RAR, it presented better results compared to SS adjuvanted with RAR.associated with RAR, it presented better results compared to SS adjuvanted with RAR.
Influence of dietary supplementation with lutein on the progression and treatment of experimental periodontitis induced in rats
Keywords: Periodontite; Doenças periodontais; Raspagem dentária; Suplementos dieteticos; Periodontitis